2008
DOI: 10.5194/acp-8-2643-2008
|View full text |Cite
|
Sign up to set email alerts
|

Variability of subtropical upper tropospheric humidity

Abstract: Abstract.Analysis of Atmospheric Infrared Sounder (AIRS) measurements for five years shows significant longitudinal variations in the winter subtropical upper tropospheric relative humidity (RH), not only in the climatological mean values but also in the local distributions and temporal variability. The largest climatological mean values occur over the central-eastern Pacific and Atlantic oceans, where there is also large day-to-day variability. In contrast, there are smaller mean values, and smaller variabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Upper level potential vorticity (PV) is a typical cause of upper level disturbances. The dynamics of PV and its relation to relative humidity (RH) and precipitation have been studied through National Centers for Environmental Prediction (NCEP)‐National Center for Atmospheric Research Reanalysis, rain gauge data, trajectories, and satellite observations such as Total Ozone Mapping Spectrometer and Atmospheric InfraRed Satellite data [ Wernli and Davies , ; Lackmann and Gyakum , ; Massacand et al , ; Waugh , ; Ryoo et al , , ; Martínez‐Alvarado et al , ]. Waugh [] showed that upper level PV often originates within dry and cold stratospheric air to the west of high PV intrusions by promoting downward motions and brings moist and warm tropospheric air to the east of high PV intrusions by inducing strong upward motions.…”
Section: Introductionmentioning
confidence: 99%
“…Upper level potential vorticity (PV) is a typical cause of upper level disturbances. The dynamics of PV and its relation to relative humidity (RH) and precipitation have been studied through National Centers for Environmental Prediction (NCEP)‐National Center for Atmospheric Research Reanalysis, rain gauge data, trajectories, and satellite observations such as Total Ozone Mapping Spectrometer and Atmospheric InfraRed Satellite data [ Wernli and Davies , ; Lackmann and Gyakum , ; Massacand et al , ; Waugh , ; Ryoo et al , , ; Martínez‐Alvarado et al , ]. Waugh [] showed that upper level PV often originates within dry and cold stratospheric air to the west of high PV intrusions by promoting downward motions and brings moist and warm tropospheric air to the east of high PV intrusions by inducing strong upward motions.…”
Section: Introductionmentioning
confidence: 99%
“…Air parcels reaching the subtropics during the cold season tend to be last saturated in the extratropical storm tracks and the associated westerly jets (Galewsky et al 2005;Kelly et al 1991;Yang and Pierrehumbert 1994). Transient potential vorticity (PV) intrusions have been linked to variability of humidity in the upper troposphere (Ryoo et al 2008), particularly over the subtropical oceans (Ryoo et al 2008;Waugh 2005;Waugh and Funatsu 2003). They attributed the aridity over the subtropical eastern Pacific to final dehydration both in the midlatitudes and in the tropical upper troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations by Dessler and Sherwood (2000) suggested the importance of realistic three-dimensional large-scale wind fields to accurately predict the variations of UTRH. Ryoo et al (2008) reported poleward advection associated with the PV intrusion as a potential mechanism for the UTRH enhancement. Consistent with this, in the present study, the wind vector at 350 K isentropic level shows the flow from low to high latitudes to the east of the PV intrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Folkins and Appenzeller (1996) and Baray et al (1998) observed sudden changes in ozone mixing ratio at tropical latitudes in connection with the PV intrusion. Ryoo et al (2008) studied the variability of subtropical UTRH during the northern winter and reported that both convection and poleward advection during PV intrusions could contribute towards increase in UTRH. However, we present four cases here, in which even tropical UTRH variations are shown to be dependent on the northward advection associated with the PV intrusions irrespective of whether the intrusions are accompanied by deep convection or not.…”
Section: Introductionmentioning
confidence: 99%